2015
DOI: 10.22205/sijbs/2015/v1/i2/100425
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Optimization Approach for Enhanced Production of Antimicrobial Compound from <I>Streptomyces rochei</I> BKM-4

Abstract: The main objective of the present work is to demonstrate the efficiency of multi-factorial experimental designs to elucidate factors affecting the antimicrobial compound production by Streptomyces rochei BKM-4 isolated from an Eastern Ghats soil. Combinations of Plackett -Burman design (PBD) and Box -Behnken design (BBD) have been carried out for the optimization of various factors for antimicrobial production. Among 9 factors, yeast extract, D-glucose and incubation periods were selected due to significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ōmura (2011) reported a wide range of secondary metabolites identified from bacteria, fungi and actinomycetes. Reports on bioactive metabolites of Streptomyces from forest soil (Balachandran et al 2015;Velayudam & Murugan 2015), marine (Sánchez López et al 2003;Rashad et al 2015) and terrestrial environments (Raju et al 2013;Duraipandiyan et al 2014) Since, the identified compound is a novel fatty acid amide derivative, comparison of its biological activity could be more reasonable with related fatty acids and its amide derivatives. Fatty acid amides and their derivatives exhibited a broad-spectrum antimicrobial activity against human pathogenic bacteria, yeasts and moulds (Novak et al 1969;Kabara et al 1972;omura et al 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Ōmura (2011) reported a wide range of secondary metabolites identified from bacteria, fungi and actinomycetes. Reports on bioactive metabolites of Streptomyces from forest soil (Balachandran et al 2015;Velayudam & Murugan 2015), marine (Sánchez López et al 2003;Rashad et al 2015) and terrestrial environments (Raju et al 2013;Duraipandiyan et al 2014) Since, the identified compound is a novel fatty acid amide derivative, comparison of its biological activity could be more reasonable with related fatty acids and its amide derivatives. Fatty acid amides and their derivatives exhibited a broad-spectrum antimicrobial activity against human pathogenic bacteria, yeasts and moulds (Novak et al 1969;Kabara et al 1972;omura et al 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Velayudham ans Murugan [20] mentioned that different glucose concentration will affect the production of antibiotics. El-sayed et al [21] also added that altering glucose concentration in fed batch culture can yield maximum production of natamycin, produced from Streptomyces natalensis.…”
Section: Antibiotic Production Optimizationmentioning
confidence: 99%